2019
DOI: 10.1039/c9mh00051h
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of super-repellent surfaces: current and future

Abstract: In this review, we critically examine the progress made in characterizing the hemocompatibility of super-repellent surfaces and identify the potential challenges and opportunities for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 196 publications
1
25
0
Order By: Relevance
“…5 a Schematic diagram of hydrophilic modification. b Surface roughness for surface wetting models [ 66 ] …”
Section: Physicochemical Modification Of the Membrane Surfacementioning
confidence: 99%
“…5 a Schematic diagram of hydrophilic modification. b Surface roughness for surface wetting models [ 66 ] …”
Section: Physicochemical Modification Of the Membrane Surfacementioning
confidence: 99%
“…70 Super-> 150°) △ < 5°) released due to the pressure of the liquid, there is a complete wetting, transitioning from Cassie state to the Wenzel state which is governed by breakthrough pressure. 73 This transition can make the surface more hydrophilic than the unmodified substrates due to the increase in overall roughness.…”
Section: Surface Properties and Their Influence In Hemocompatibilitymentioning
confidence: 99%
“…Super-repellent surfaces are surfaces that repel most liquids as their surface energy is significantly lower. 97 Although hydrophilicity has been widely employed for blood-contacting medical devices, recent research has shown even lower protein adsorption and platelet adhesion on superhydrophobic surfaces. 98 Superhydrophobicity can be achieved by combination of surface texture (e.g., micro and/or nanoscale texture) and coating with low surface energy compounds.…”
Section: Super-repellent Surfacesmentioning
confidence: 99%
“…Liquid-repellent surface technologies are studied extensively for a wide range of applications, such as waterproofing, anti-icing, antistaining, anti-biofouling and self-cleaning. [1][2][3][4][5][6] Superhydrophobic and superoleophobic surfaces are often prepared through a combination of topography, such as ordered arrays of nano-or microstructures or fibrous textures, and chemical functionality, fluorination, for example. 1,7 On these lotus-like surfaces, droplets interact with the surfaces and the air trapped between the features of the surfaces, resulting in discontinuous and unstable surface-liquid contact lines (Fig.…”
Section: Introductionmentioning
confidence: 99%